PERAN KELEMBAGAAN MASYARAKAT DALAM PENGELOLAAN DESA WISATA DAYUN KECAMATAN DAYUN KABUPATEN SIAK - Ginting, Okta Fiani Br.; Sidiq, Rd. Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to find out the Role of Community Institutions in the Management of Dayun Tourism Village, Dayun District, Siak Regency, Dayun Tourism Village is one of the community-based tourist destinations that focuses on cultural preservation and the utilization of local potential. The institutional role of the community in this village is vital in supporting sustainable tourism development. Village institutions, such as tourism awareness groups (Pokdarwis), associations, art studios, customary institutions, fire care communities, waste management institutions, Bumkam, farmer groups, UMKM, livestock groups, Customary Institutions, Bapekam, function as the main driving force in preserving cultural values, environmental management, and improving the community's economy. Through collaboration between the community, government, and the private sector that is participatory and innovative. In this study, the data collection techniques used are observation, interviews, and documentation.based on the results of the research, it can be concluded that the challenges faced include limited human resources, funding, and infrastructure. However, synergy between various stakeholders is the key in realizing a dayun tourism village as a resilient and sustainable community-based tourism model. Keywords: Dayun Tourism Village, Community Institutions, Community-Based Tourism, cultural preservation, sustainable management.